2018
DOI: 10.1063/1.5053559
|View full text |Cite
|
Sign up to set email alerts
|

High and low density patches in simulated liquid water

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 82 publications
4
67
0
Order By: Relevance
“…Using the Voronoi-void network we have found that liquid water is characterized by a large proportion of small spherical voids and large fractal or dendritic like voids at ambient conditions. 44 Voids have allowed us to identify the inhomogeneities in density, generated by fluctuations in a manner where anisotropies can be seen in a very chemically intuitive manner. The use of Voronoi-voids to examine the role of geometry on packing in simple liquids has previously been highlighted by Sastry and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Voronoi-void network we have found that liquid water is characterized by a large proportion of small spherical voids and large fractal or dendritic like voids at ambient conditions. 44 Voids have allowed us to identify the inhomogeneities in density, generated by fluctuations in a manner where anisotropies can be seen in a very chemically intuitive manner. The use of Voronoi-voids to examine the role of geometry on packing in simple liquids has previously been highlighted by Sastry and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Different local and global order parameters have been used in order to assess the presence of low-and highdensity regions in liquid water 26,27 . Recently, coexisting low-and high-density regions in ambient water have been identified using Voronoi voids on a larger length scale of 1-2 nm than those predicted by local order parameters and those reported previously 19 . Atomistic simulations showed that the low-and high-density regions are formed around the regions of empty space within the hydrogen-bond network, occurring as a result of thermal fluctuations 18 .…”
Section: E Zakhvataev 12* and L A Kompanietsmentioning
confidence: 71%
“…It should be noted that in many cases density variations will have sizes both smaller and larger than the indicated average size 8,16 . (iii) The length scale of low-and high-density regions in ambient water identified using Voronoi voids was found to be 1-2 nm 19 .…”
Section: Resultsmentioning
confidence: 92%
“…In order to identify the above mentioned cages, we have used a methodology based on the Voronoi S-network, which is a generalization of the Voronoi-Delaunay tessellation for multicomponent systems [30][31][32][33] . This approach has been used in the past to identify regions of empty space in semiconducting alloys 34 , to study density fluctuations in supercooled liquids [35][36][37] and even to investigate proton diffusion in water 38 . The relevant methodological details can be found in Refs.…”
Section: Methodsmentioning
confidence: 99%